CULTIVATION OF MELISSA OFFICINALIS L. PLANT SEEDLINGS UNDER DIFFERENT CONDITIONS - Usmonov , Tokhirjon Zokirjon ugli; Zahiriddinov , Ilyosjon Ilhomjon ugli; Kodirova , Husnida Mahsutali kizi; Shomansurov , Shokarim Shobahrom ugli; Solijonov, Shahboz Zafarjon ugli (Educational Research in Universal Sciences, 2024)
In the experiment, we developed the technology of growing a medicinal lemon plant. In the experiment, when the seeds of the lemon plant were planted in different conditions and norms, the variants using humus recorded higher indicators compared to the seeds planted in natural soil conditions. Since plant seeds are grown in soils with good permeability of air, heat, moisture and low soil density (biohumus soil), the transition of seeds to development phases has accelerated.